(untitled) (Journal of Comparative Social Work, 2012)
Comparative research on welfare states is facing various pitfalls in our days. This article is concerned with a particularly tricky issue by considering scholastic effects of thinking welfare provision in terms of typologies, such as the one developed by Esping-Andersens in his study on The Three Worlds of Welfare Capitalism.